Optimization of condition of target irradiation for radionuclide production - Dovbnya, A.M.; Shramenko, B.I.; Torgovkin, A.V. (Вопросы атомной науки и техники, 2004)
In this report the different target arrangement relative to the bremsstrahlung beam have been considered. The analyses of spectral and angular distributions of bremstrahlung from different targets and as function of incident electron energy have been done. The worked out activity dependence on parameters of radionuclide target and bremstrahlung converter has been investigated. The different target arrangements relative to the bremsstrahlung beam have been considered. The analyses of spectral and angular distributions of bremstrahlung from different targets and as function of the incident electron energy have been done. The worked out activity dependence on parameters of a radionuclide target and a bremsstrahlung converter has been investigated. The recommendations concerning the optimal bremsstrahlung converter and target arrangement intention and the beam efficiency have been developed.